Focused Group Interview Literature Review of Challenges Ethiopian Female Entrepreneurs Face in their Business Ventures - Kant, Shashi; Metasebia Adula (RADINKA JAYA UTAMA PUBLISHER, 2023)
This study aims to investigate the difficulties female business owners face in the Bule Hora town administration in Ethiopia's Horn of Africa. Due to problems with how women are regarded, treated, and considered to be, there is a difference between inactive women and those who have potential. The researchers used a qualitative research design and an interpretative research technique. The researchers spoke with eight female business owners engaged in the company's founding. The purposive sample strategy was used using a structured interview to gather primary data from the respondents. For the analysis of qualitative data, thematic data analysis was used. The primary conclusions of the study showed that social and cultural barriers, lack of money, a lack of adequate employment prospects, a lack of expertise, and a lack of training were the biggest challenges for women entrepreneurs in the study area. The study's conclusions will help the government as it updates its policies to address organizational, individual, legal/administrative, economic, social/cultural, and other aspects that affect how women entrepreneurs view entrepreneurship.